Complete poems - Pratt, E. J. (Edwin John), 1882-1964 (Pratt, E. J. (Edwin John), 1882-1964. Works. 1983., 1989)
This volume of E.J. Pratt's selected poems introduces Pratt's poems to the college and university student, providing the background necessary for an informed reading of the poems. The volume offers a full sampling of Pratt's poems chosen both for their representativeness and for their intrinsic value. Included are the major long poems, The Witches' Brew, The Iron Door, The Titanic, Brébeuf and His Brethren, and Towards the Last Spike, and important shorter lyrics such as 'Newfoundland,' 'Come Away, Death,' and 'From Stone to Steel.' The editorial approach is historical, chronological, and biographical. The introduction locates E.J. Pratt in his Newfoundland and Canadian contexts, and discusses the development of his work in relation to his early modernist contemporaries, concluding that Pratt remains the most important and influential Canadian poet up to the mid-fifties. As such, he has been a key figure in shaping the Canadian literary imagination of his day and the later poetics of landscape adopted by Earle Birney and Margaret Atwood. The editors provide annotations, textual notes, and a biographical chronology. The printed volume is supplemented by the electronic resources of the Selected Pratt website at www.trentu.ca/pratt/selected.